Analysis of Market Potential Development of Al-Amin Science and Industrial Park (Living Lab) Glugur Rimbun Area in Kutalimbaru District, Deli Serdang Regency - Hidayati Purnama Lubis; Dewi Mahrani Rangkuty; Dian Yulis Wulandari; Ika Andryani (Universitas Kristen Indonesia Toraja, 2023)
Al-Amin Science And Industrial Park (Living Lab) area is located in Glugur Rimbun, Sampe Cita Village, Kutalimbaru District, in Deli Serdang Regency, North Sumatra Province. This land area is approximately 20 hectares and is owned by the Panca Budi Development University Foundation. Initially, this area is in the form of an Oil Palm plantation, it will be developed into an Industrial Estate oriented to Science and Nature Laboratories. The methods used are qualitative methods of literature studies and field studies. There is a considerable market opportunity in the development of the area so that it can provide benefits and profit benefits for stakeholders and the community in Kutalimbaru District, that is, the most popular product is the development of the Agricultural Area by 28%, followed by the Livestock Area by 22%. As for each of them, 9% of the public interest is in the development of Nature Tourism Areas, Educational Tourism, and Open Learning Spaces (Nature Schools). The remaining 7% of people are interested in the Selfie Area. The Tarekat Museum area and Restaurants and Cafes are in demand by only 6% and for the Development of Edutech Tourism Areas are in demand by 4%.